Detection of Hemoglobin D in Tharu Community of Banke, Nepal - Gupta, Sharmila; Kapoor, A. K. (Journal of Nepalgunj Medical College, 2017)
Background: Patients presenting with microcytic anemia, hepatosplenomegaly, abnormal hemoglobin level in electrophoresis and negative sickling test should have high suspicion for HbD disease. This occurrence is more in certain communities. While investigating the etiopathogenesis of subjects with microcytic anemia (n=30), we came across 3 patients with HbD disease. Aim: Present study describes the clinical and hematological findings of 3 patients. Material and Methods: This was an observational study conducted between August, 2014 to July, 2015 in Department of Pathology of Nepalgunj Medical College. Of 30 patients diagnosed as microcytic anemia, 3 patients were selected. Results : The patients belonged to Tharu Chaudhary community of Banke district of Nepal. Age of the patients ranged from 8 to 13 years. All the patients had generalized pallor. Two of 3 patients had fever, joint pains and jaundice. One of the patients had hepatosplenomegaly. Total hemoglobin ranged from 7.1 to 8.4 gm/dl. Patients had microcytic anemia. Sickling test was negative in all the 3 patients. Hemoglobin (Hb) electrophoresis revealed peaks in HbS region. Due to negativity of sickling test, the abnormal hemoglobin peak was interpreted as HbD. Thus, 2 patients had homozygous HbD disease while another patient had heterozygous HbD trait. JNGMC Vol. 14 No. 1 July 2016